1999
DOI: 10.1139/g98-129
|View full text |Cite
|
Sign up to set email alerts
|

Identification of AFLP markers closely linked to the powdery mildew resistance genes Pm1c and Pm4a in common wheat (Triticum aestivum L.)

Abstract: A total of 7654 DNA fragments were screened for linkage to wheat powdery mildew resistance gene Pm1c employing fluorescently based AFLP analysis and phenotypic pools from F3 families. F3 and derived F4 families were used for segregation analysis. Pool screening revealed several cosegregating and tightly linked (0.9 cM) AFLP markers for the Pm1c resistance gene. The previously reported RFLP locus Xwhs178 was integrated into the AFLP map in the vicinity of Pm1c. One AFLP marker, 18M2, was determined to be highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 0 publications
0
54
0
Order By: Relevance
“…Earlier AFLP-based marker studies have been found to be informative in assessment of genetic diversity in wheat varieties started in 1998 [70,71]. Regarding the investigation of traits associated with yield, Goodwin et al [72] and Hartl et al [73] initiated the AFLP technique to develop an AFLP marker associated with resistance to Septoria tritici blotch and powdery mildew, respectively. Hartl et al identiied several AFLP markers closely linked to the Pm1c and Pm4a [73].…”
Section: Ampliied Fragment Length Polymorphism (Aflp) Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier AFLP-based marker studies have been found to be informative in assessment of genetic diversity in wheat varieties started in 1998 [70,71]. Regarding the investigation of traits associated with yield, Goodwin et al [72] and Hartl et al [73] initiated the AFLP technique to develop an AFLP marker associated with resistance to Septoria tritici blotch and powdery mildew, respectively. Hartl et al identiied several AFLP markers closely linked to the Pm1c and Pm4a [73].…”
Section: Ampliied Fragment Length Polymorphism (Aflp) Markersmentioning
confidence: 99%
“…Regarding the investigation of traits associated with yield, Goodwin et al [72] and Hartl et al [73] initiated the AFLP technique to develop an AFLP marker associated with resistance to Septoria tritici blotch and powdery mildew, respectively. Hartl et al identiied several AFLP markers closely linked to the Pm1c and Pm4a [73]. Out of 92 AFLP primer combinations, 31 polymorphic fragments detected between the resistance and susceptible lines, of which eight were found to be the most reliable polymorphic markers.…”
Section: Ampliied Fragment Length Polymorphism (Aflp) Markersmentioning
confidence: 99%
“…DNA quantity and quality were assessed with a UV-Photometer. The AFLP analysis was performed in a similar way to that described by Hartl et al (1999) using the enzyme combination Sse8387I and MseI. Thirty Sse8387I+NN/MseI+NN primer combinations with two selective nucleotides on the 3 ‫׳‬ -end of both primers were used for selective PCR amplification.…”
Section: Genomic Dna Extraction Aflp and Ssr Markersmentioning
confidence: 99%
“…High reproducibility, rapid generation, and high frequency of identifiable polymorphisms make the amplified fragment length polymorphism (AFLP) analysis (Vos Pieter et al, 1995) an attractive technique for indentifying polymorphic markers linked to important traits by analyzing individuals from segregating populations (Goodwin et al, 1998;Hartl et al, 1999). However, AFLP analysis is tedious and time-consuming since it involves several steps: DNA digestion, ligation, preamplification, and selective amplification.…”
Section: Introductionmentioning
confidence: 99%